The changes of soft tissue profile in skeletal class II patients with mandibular retrognathy treated by the extraction of maxillary first premolars - Hendri, H.; Hambali, Tono S.; Salim, Jono; Mardiati, Endah (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The purpose of this research is to measure the change of soft tissue profile, both anteroposteriorly as well as vertically in skeletal class II patients with mandibular retrognathy cases, treated with extraction of the maxillary first premolars. Pre and post treatment result of 16 patient treated with the Standard Edgewise fixed appliance were compared using a Canon D646u series scanner and Corel Draw 12 computer programme, utilizing the TVL line as a plane of orientation. The result was analyzed with a paired t-test. Statistical analysis shows significant anteroposterior and vertical soft tissue changes in facial profile in skeletal class II patients with mandibular retrognathy treated with extraction of maxillary first premolars using the Standard Edgewise fixed appliance, measured with the STCA-VTL method.